When Software Engineering Meets Quantum Computing. - ALI, SHAUKAT; YUE, TAO; ABREU, RUI (Communications of the ACM, 2022)
The article examines the design of software for quantum computing. The application of quantum computing for drug discovery and vaccine development is described along with efforts at European research centers to build ion-trapped and 100-qubit supercomputer and alleged idiosyncrasies associated with testing and debugging quantum software.